2020
DOI: 10.1016/j.cgh.2020.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polygenic Risk Scores to Select Screening Intervals After Negative Findings From Colonoscopy

Abstract: BACKGROUND & AIMS: Polygenic risk scores (PRSs) could help to define starting ages for colorectal cancer (CRC) screening. However, the role of PRS in determining the length of screening interval after negative findings from colonoscopies is unclear. We aimed to evaluate CRC risk according to PRS and time since last negative colonoscopy. METHODS: We collected data from 3827 cases and 2641 CRC-free controls in a population-based casecontrol study in Germany. We constructed a polygenic risk scoring system, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that PRS-based assessment of genetic risk has the potential to identify low-and high-risk populations and might help guide personalized recommendations on starting age for CRC screening and time intervals between repeat screening colonoscopies. [8][9][10] Focusing screening colonoscopy on those at highest risk may enable offering screening colonoscopy in countries with limited resources, and riskadapted screening might make screening colonoscopy even more cost effective or cost saving in countries with sufficient colonoscopy capacities. Besides risk-adapted definition of starting ages of screening and time intervals between repeat screening colonoscopies, riskadapted definitions of surveillance intervals after detection and removal of adenomas might further enhance the most efficient use of colonoscopy resources and reduce the possibility of overusing surveillance colonoscopy among people with low risk and underusing among people with high risk, which are major issues in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that PRS-based assessment of genetic risk has the potential to identify low-and high-risk populations and might help guide personalized recommendations on starting age for CRC screening and time intervals between repeat screening colonoscopies. [8][9][10] Focusing screening colonoscopy on those at highest risk may enable offering screening colonoscopy in countries with limited resources, and riskadapted screening might make screening colonoscopy even more cost effective or cost saving in countries with sufficient colonoscopy capacities. Besides risk-adapted definition of starting ages of screening and time intervals between repeat screening colonoscopies, riskadapted definitions of surveillance intervals after detection and removal of adenomas might further enhance the most efficient use of colonoscopy resources and reduce the possibility of overusing surveillance colonoscopy among people with low risk and underusing among people with high risk, which are major issues in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…7 We calculated a weighted PRS by summing the product of the reported regression coefficients and number of risk alleles (0, 1, and 2) across the 140 SNPs for all study participants. In line with previous studies, [8][9][10] participants were categorized further into 3 groups (low, medium, or high PRS) according to tertiles of the PRS among controls.…”
Section: Implications For Patient Carementioning
confidence: 98%
See 1 more Smart Citation
“…4 When applied to cancer screening, it may impact the age at which someone commences screening, screening intervals, and the type of test used. [5][6][7] Focusing screening on those most at risk may be more cost-effective and avoid the potential sequelae of false positives and overdiagnosis for individuals who fall into lower-risk categories. 8,9 Clinical trials are actively investigating how PRS guided screening compares with conventional screening for breast and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…703/2010, the "Ethikkommission Burgenland", KRAGES, 33/2010; and the Institute of Experimental Medicine in Prague, Czech Republic). Information about these four populations has been described in detail elsewhere [3,[19][20][21][22].…”
Section: Study Populationsmentioning
confidence: 99%